Analisis Peran Zakat Produktif di Kampung Zakat Desa Sulung dengan Metode Center of Islamic Business and Economic Studies-IPB - Sukmawati, Urai Sulia; Paizal, Muhamad; Srihani, Srihani; Perdana, Wahyu (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2023)
One of the complex problems in Indonesia that is difficult to solve is poverty.  In Islam, zakat can be used as a solution in poverty alleviation. The Ministry of Religious Affairs together with the National Amil Zakat Agency In 2018 cooperated in organizing zakat villages, initially there were only 7 zakat villages nationwide and Sulung village was selected as the only zakat village in West Kalimantan. In a study entitled Analysis of the Role of Productive Zakat in Kampung Zakat Sulung Village With the CIBEST Method. Researchers aim to examine the role of zakat in improving mustahik welfare, this research is a quantitative study with a Cibest model approach with primary data. The results showed that before the zakat village program, the 7 mustahik were in quadrant 1 which means materially poor but spiritually rich, while the changes obtained after receiving productive zakat, the 7 mustahik families experienced changes, namely 5 mustahik families shifted to quadrant II i.e. spiritual and material well-being.